Development of a questionnaire library for rapid health data acquisition during wildfire events - Lilian Liu; Christine Loftus; Diana Rohlman; Edmund Seto; Elena Austin (MethodsX)
Rapid health outcome data acquisition using existing questionnaires can accelerate time-sensitive wildfire research. We intended to create a health questionnaire library that contains readily deployable questionnaires for researchers, public health agencies, and other groups interested in rapid data collection during wildfire events. In this paper, we describe the methodology used to identify relevant self-reported health questionnaires and develop the structured questionnaire library, which serves as a centralized platform for wildfire researchers seeking to quickly design health assessment instruments. This method can also facilitate rapid questionnaire-based data collection following other disasters. To do so we performed the following tasks: • A systematic literature review of wildfire exposure and health studies to 1) identify health outcome categories associated with wildfire and smoke exposure and 2) extract questionnaires used for health outcomes related to wildfire exposure. • A secondary search of existing questionnaire repositories to identify additional relevant health instruments. • A structured organization of questionnaires (n = 100) by eight health outcome categories (mental health = 60, respiratory health = 19, overall health = 17, sleep = 10, cardiovascular health = 4, allergy = 1, irritation (eye, throat, skin) = 2, and metabolic health = 1) into a wildfire health questionnaire library.